2014
DOI: 10.1126/science.1253138
|View full text |Cite
|
Sign up to set email alerts
|

A memory of errors in sensorimotor learning

Abstract: The current view of motor learning suggests that when we revisit a task, the brain recalls the motor commands it previously learned. In this view, motor memory is a memory of motor commands, acquired through trial-and-error and reinforcement. Here we show that the brain controls how much it is willing to learn from the current error through a principled mechanism that depends on the history of past errors. This suggests that the brain stores a previously unknown form of memory, a memory of errors. A mathematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
422
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 314 publications
(516 citation statements)
references
References 38 publications
(36 reference statements)
39
422
5
Order By: Relevance
“…The sensitivity-to-error model proposed by Herzfeld et al (2014) cannot account for all of our results, however. In particular, it predicts that adaptation rate upon reexposure to a given perturbation will steadily increase as the duration of the initial exposure to the perturbation increases, even after one reaches asymptote.…”
Section: Discussioncontrasting
confidence: 41%
See 4 more Smart Citations
“…The sensitivity-to-error model proposed by Herzfeld et al (2014) cannot account for all of our results, however. In particular, it predicts that adaptation rate upon reexposure to a given perturbation will steadily increase as the duration of the initial exposure to the perturbation increases, even after one reaches asymptote.…”
Section: Discussioncontrasting
confidence: 41%
“…A recent study suggested that savings may not be due to recall of prior actions but rather might be due to an underlying sensory-error-driven learning process increasing its sensitivity to previously experienced errors (Herzfeld et al 2014). The authors of that study showed that experiencing a particular error at one time leads to a durable change in response to the same or similar errors in the future.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations